Protecting the health of the elderly : a review of WHO activities - Skeet, Muriel; World Health Organization (Copenhagen : World Health Organization, Regional Office for Europe ; Albany, N.Y. : Obtained from WHO Publications Centre USA, 1983)
Hoe beschermen we de gezondheid van onze ouderen?
Bibliography: p. 121-123.
Keywords: Aging -- Congresses; Aging -- Europe -- Congresses; Community health services for older people -- Congresses; Community health services for older people -- Europe -- Congresses; Older people -- Health and hygiene -- Congresses; Older people -- Health and hygiene -- Europe -- Congresses; Conference papers and proceedings